Pemberian Serbuk Daun Kelor (Moringa oleifera) terhadap Perbaikan Profil Lipid dan Ketebalan Aorta pada Tikus Model Prediabetes Mellitus: Pemberian Serbuk Daun Kelor terhadap Perbaikan Profil Lipid dan Ketebalan Aorta pada Tikus Model Prediabetes Melitus - Ariestiningsih, Ayuningtyas Dian; Cempaka, Anggun Rindang; Kusumastuty, Inggita; Cahyaningrum, Aladhiana; Setiawati, Sindi; Arintya, Diandra; Azmi, Ulul; Salwa, Putri; Malahayati, Huzaifah; Wibowo, Rizka Azhari; Handayani, Dian (Universitas Airlangga, 2024)
Background: Consumption of beverages and processed foods with high fructose content has increased recently. This condition increases the risk of metabolic syndrome, which include insulin resistance, impaired lipid profile, and elevated blood pressure. Moringa leaves (Moringa Oleifera), with their bioactive compounds that function as antioxidants, are known to improve fat metabolism and blood glucose. Objectives: The purpose of this study is to analyze the effect of Moringa Oleifera leaf powder and quercetin in controlling metabolic syndrome conditions by improving lipid profiles and aortic thickness in prediabetes mellitus (pre DM). Methods: This experimental research used a post-test-only control group design approach. A total of 35 male Wistar rats were divided into 5 groups such as group K0 (standard feed), E1 (66% fructose probe for 16 weeks), E2 (66% fructose probe for 12 weeks), E3 (66% fructose probe + quercetin 50 mg/kgBW), and E4 (66% fructose probe + Moringa leaf powder 500 mg/kgBW). The examination method for lipid profiles involved serum extraction and enzymatic tests, weighing for white fat tissue mass, while the aorta was examined using a light microscope and histological image analysis. Data analysis used the One-Way ANOVA test. Results: This research showed there are no difference in triglycerides, Low-Density Lipoprotein (LDL) cholesterol, and white adipose tissue significantly between the treatment groups. Level of High-Density Lipoprotein (HDL) cholesterol, total cholesterol, and aortic thickness between the treatment groups are significant differences, with the best results sequentially in groups E2, E1, and K0. Conclusions: The administration of Moringa leaf powder for 4 weeks showed improvements in lipid profiles and aortic thickness in prediabetes mellitus conditions.